ULAMA BOGOR DALAM PENGEMBANGAN TRADISI INTELEKTUAL: - Fakhriati Fakhriati (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
As other ulamas generally, Bogor ulamas were responsible in developing the intellectual tradition of their society. This tradition was surely influenced by the local Sundanese culture where these ulamas held the central roles. However, the turning time, globalisation, and the borderless society had parsed local Sundanese cultures. This had served as a challenge for Bogor ulamas in maintaining the intellectual tradition with its religious and local nuances. As the cultural brokers, these ulamas’ writings were evidence of their efforts in maintaining the written tradition based on the local cultures and also on the current changes. This paper discusses the efforts taken by Bogor ulamas living in the 20th and the 21st centuries in building their intellectual tradition and adapting to the changes. Finally, it finds out that there are some discrepancies between the intellectual products of the past and the contemporary ulamas either in the content or in the languages as one form of local culture conservation.